Changes in Rainfall and Climate Classification in South Sulawesi - Ridahwati Ridahwati (Journal La Lifesci, 2021)
The study discuss about Changes in Rainfall and Climate Classification in South Sulawesi. The climate of the Earth is determined by the location of the sun in relation to the earth's surface. Geographical location influences the categorization of climate on our planet. The results of the study (1) Rainfall in Bone Regency has been classified as high rainfall intensity for the last 10 years; (2) Determination of climate classification can be done by processing rainfall data obtained from data before weighting, after weighting, ranking, and opportunity; (3) The climate classification according to Schmidt-Ferguson for Bone Regency has a B climate type, which is a humid subtropical climate; and (4) The climate classification according This is based on a comparison of the number of dry months (BK) and wet months (BB), from which the Q value is obtained, which is then used to determine the type of climate according to Schmidt-Ferguson; (4) Oldeman's climate classification for Bone Regency has a C1 climate type, which has the characteristics of planting lowland rice once a year and secondary crops twice a year; (5) Oldeman's climate classification for Bone Regency has a This is based on the number of Wet Months (BB) and Dry Months (BK) in a given year